Development, Safety, and Therapeutic Evaluation of Voriconazole-Loaded Zein–Pectin–Hyaluronic Acid Nanoparticles Using Alternative In Vivo Models for Efficacy and Toxicity - Fin, Margani Taise; dos Santos, Kelvin Sousa [UNESP]; Gualque, Marcos William de Lima [UNESP]; dos Santos, Rafaela Cristine [UNESP]; Aoki, Natália Cristina Morici [UNESP]; Auler, Marcos Ereno; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Gianinni, Maria José Soares [UNESP]; Mainardes, Rubiana Mara (MDPI, 2025)
Background/Objectives: Fungal infections caused by Candida species remain a significant clinical challenge, exacerbated by limitations in current antifungal therapies, including toxicity and poor bioavailability. This study aimed to develop and evaluate voriconazole-loaded zein–pectin–hyaluronic acid nanoparticles (ZPHA-VRC NPs) as a novel drug delivery system to enhance efficacy and reduce toxicity. Alternative in vitro and in vivo models were utilized to assess the safety and therapeutic potential of the nanoparticles. Methods: ZPHA-VRC NPs were prepared using a nanoprecipitation method and characterized for particle size, polydispersity index, zeta potential, and encapsulation efficiency. Antifungal activity was assessed via MIC assays against Candida albicans, C. krusei, and C. parapsilosis. Cytotoxicity was evaluated on Vero cells, while in vivo toxicity and efficacy were assessed using Galleria mellonella and Caenorhabditis elegans models. The therapeutic efficacy was further evaluated in an infected Caenorhabditis elegans model using survival and health scores. Results: ZPHA-VRC nanoparticles exhibited favorable physicochemical properties, including a particle size of approximately 192 nm, a polydispersity index of 0.079, a zeta potential of −24 mV, and an encapsulation efficiency of 34%. The nanoparticles retained antifungal activity comparable to free voriconazole while significantly reducing cytotoxicity. In vivo studies using G. mellonella and C. elegans demonstrated that ZPHA-VRC NPs markedly improved survival rates, reduced fungal burden, and enhanced health scores in infected models, outperforming the free drug. Additionally, the nanoparticles exhibited a superior safety profile, minimizing systemic toxicity while maintaining therapeutic efficacy. Conclusions: ZPHA-VRC NPs offer a safer and more effective delivery system for VRC, addressing the limitations of conventional formulations. The integration of alternative efficacy and safety models highlights their value in preclinical research.
Keywords: antifungal therapy; Caenorhabditis elegans; Candida infections; Galleria mellonella; nanoparticles; voriconazole